Heterologous expression of recombinant scygonadin antimicrobial peptide from mud crab Scylla serrata - Nurfarhana Rosli,; Farah Ayunie Mohd Zain,; Sandra Catherine Zainathan,; Siti Nor Khadijah Addis, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Antimicrobial peptides (AMPs) are the most common immune effectors in invertebrates that functions as the first line of defence against microbial infection. Scygonadin is an AMP which can be found in the seminal plasma of Scylla serrata. Preceding studies had shown that scygonadin have the ability to exhibit wide antimicrobial activities. Nonetheless, analysis of the antimicrobial properties of scygonadin is significantly dependent on acquiring sufficient amounts of the protein from mud crab, and this was proven difficult. Further functional studies of scygonadin and its commercial applications require a development of efficient, sustainable and cost-effective heterologous protein production. To address this issue, an expression plasmid containing 387 bp of scygonadin gene of Scylla serrata was cloned into pBAD/Myc-His A, expressed in TOP10 cells with L-arabinose as expression inducer, followed by protein purification by using immobilized metal affinity chromatography (IMAC). The optimal expression condition was determined by incubation with 0.02% of L-arabinose for 4 hours at 37°C. A total of 2 mg/ml of purified scygonadin with the molecular weight of ~17kDa was succesfully obtained. The results demonstrated that the recombinant scygonadin was successfully produced in heterologous expression system which may allow production of scygonadin in large quantities for further research and commercial application.